(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. 1. Nuovi orizzonti - 2. Un caso positivo di secolarizzazione - 3. Codice del Terzo settore e iniziative caritative della comunità ecclesiale - 4. Opportunità aperte da un’alternativa - 5. L’azione caritativa tra diritto speciale e diritto comune. ABSTRACT: Except for the matter of the clergy sustenance, the current discipline of the Concordat on ecclesiastical institutions is still affected, in spite of everything, by the conditioning deriving from juridical schemes dating back in time, which sacrifice and make precarious their solidarity activities. The fall of the diffidence of the Italian legal system towards the initiatives between the State and the Market, and therefore the recent reform of the Third sector with the enhancement of the non-profit organization’s activities, represent a precious opportunity for the charitable initiatives of the ecclesial communities.